2013
DOI: 10.2527/jas.2013-6609
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the association of serum IGF-I concentration, potential candidate genes, and fiber type composition with variation in residual feed intake in progeny of Red Angus sires divergent for maintenance energy EPD1

Abstract: Investigating the genetic and physiological drivers of postweaning residual feed intake (RFI) and finishing phase feed efficiency (FE) may identify underlying mechanisms that are responsible for the variation in these complex FE traits. The objectives were 1) to evaluate the relationship of serum IGF-I concentration and muscle gene expression with postweaning RFI and sire maintenance energy (MEM) EPD and 2) to determine fiber type composition as it relates to postweaning RFI and finishing phase FE. Results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…reported that the genetic relationship between plasma IGF-I concentration and RFI becomes less positive as cattle mature physiologically. Thus, the genes associated with systemic IGF-I concentration differ between the post-weaning and finishing stages of development 43 . As a consequence, the concentration of serum IGF-1 may not be an appropriate indicator of RFI in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…reported that the genetic relationship between plasma IGF-I concentration and RFI becomes less positive as cattle mature physiologically. Thus, the genes associated with systemic IGF-I concentration differ between the post-weaning and finishing stages of development 43 . As a consequence, the concentration of serum IGF-1 may not be an appropriate indicator of RFI in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of circulating concentrations of IGF-I, some studies have reported higher (Nascimento et al, 2015), others lower (Lancaster et al, 2008) or no difference (Lawrence et al, 2012;Welch et al, 2013) in concentrations between lowand high-RFI cattle. Plasma concentrations of insulin at the end of a test period were found to be higher in the steer progeny of high-compared with low-RFI parents (Richardson et al, 2004).…”
Section: Nutrient Partitioning: Protein and Fat Depositionmentioning
confidence: 99%
“…However, the systemic IGF-I concentration is known to be influenced by environment also [7] [14]. In the contrary, a positive genetic relationship between plasma IGF-I level and RFI in sheep [35] has been reported. RFI DEGs may not be comparable with respect to age, breed and physiological status.…”
Section: System Biology Analysismentioning
confidence: 99%